IMPLEMENTATION STRATEGIES FOR MULTICULTURAL EDUCATION IN SOCIAL SCIENCE LEARNING IN JUNIOR HIGH SCHOOL - Hadi Wiyono (Jurnal Scientia, 2023)
This article encourages the need for inclusive learning strategies to accommodate cultural diversity, particularly through the implementation of multicultural education. Through the literature study method, this article reviews the implementation strategy of multicultural education in social studies learning in junior high school. Key focuses include the design of multicultural curricula, the use of diversified learning materials, and the application of inclusive teaching methods. In the context of curriculum design, research identifies the need to include cultural, historical, and values perspectives from different ethnic, religious, and social backgrounds. This implementation can enable students to understand cultural diversity thoroughly. In addition, the selection and use of diverse learning resources is key, including textbooks, articles, videos, and other resources that reflect cultural diversity. Research also highlights inclusive teaching methods as an important approach to ensuring the participation of all students. Group discussions, collaborative projects, and problem-based activities are considered effective strategies in creating an inclusive learning environment. Although the importance of multicultural education is generally recognized, its implementation has not been evenly distributed across different junior high schools. Therefore, this study aims to provide in-depth insight into the strategies and factors that influence this implementation, with the hope that it can contribute to improving the effectiveness of education and character development of students in Indonesia which is increasingly complex. Keywords: Educational, Cultural, Multicultural, Curriculum